Thermalization and Nonequilibrium Steady States in a Few-Atom System - Mayer, Daniel; Widera, Artur (Zeitschrift für Naturforschung Section A - A Journal of Physical Sciences, 2020)
We investigate nonequilibrium steady states in an isolated system of few ultracold cesium atoms (Cs). Numerically and experimentally, we study the dynamics and fluctuations of the extracted position distributions and find the formation of nonthermal steady states for absent interactions. Atomic collisions in the s-wave regime, however, ensue thermalization of the few-particle system. We present numerical simulations of the microscopic equations of motion with a simple representation of the s-wave scattering events. Based on these simulations, a parameter range is identified, where the interaction between few atoms is sufficiently strong to thermalize the nonequilibrium steady state on experimentally accessible time scales, which can be traced by monitoring the atomic position distribution. Furthermore, the total energy distribution, which is also accessible experimentally, is found to be a powerful tool to observe the emergence of a thermal state. Our work provides a pathway for future experiments investigating the effect interactions in few-particle systems and underlines the role of fluctuations in investigating few-particle systems.
CRIS-Team Scopus Importer:2023-03-27
Keywords: Few-Particle System; Nonequilibrium; Thermalization; Ultracold Atoms